Mutagenesis of the nucleocapsid protein of nipah virus involved in capsid assembly. - Swee, Tin Ong; Yusoff, Khatijah; Chiew, Ling Kho; Abdullah, Janna Ong; Wen, Siang Tan (Society for General Microbiology, 2009)
The nucleocapsid protein of Nipah virus produced in Escherichia coli assembled into herringbone-like particles. The amino- and carboxy-termini of the N protein were shortened progressively to define the minimum contiguous sequence involved in capsid assembly. The first 29 aa residues of the N protein are dispensable for capsid formation. The 128 carboxy-terminal residues do not play a role in the assembly of the herringbone-like particles. A region with amino acid residues 30–32 plays a crucial role in the formation of the capsid particle. Deletion of any of the four conserved hydrophobic regions in the N protein impaired capsid formation. Replacement of the central conserved regions with the respective sequences from the Newcastle disease virus restored capsid formation.